ANALISIS RESIKO USAHATANI KELAPA SAWIT DI DESA POLANTO JAYA KECAMATAN RIO PAKAVA KABUPATEN DONGGALA - I Komang Suparte; Arifuddin Lamusa; M Fardal Pratama (Universitas Tadulako, 2022)
The purpose of this study is to determine the magnitude of the production and income risks experienced by oil palm farmers, as well as the efforts that need to be made by farmers in mitigating production and income risks. This research was conducted in Polanto Jaya, Rio Pakava District, Donggala Regency. The location of the research was determined by purposive sampling with the consideration that this area is one of the largest oil palm producing areas in Dongala Regency. The time of the study was carried out from June to July 2021. The method of determining respondents was carried out using a simple random sample method or simple random sampling with a total of 38 respondents. The data analysis method used income analysis, coefficient of variation (CV) analysis, and descriptive analysis. The results of this study indicate that the average income of farmers in Polanto Jaya Village is Rp. 23,470,541,/Ha/Year. The production risk obtained by the Coefficient of Variation (CV) of 0.0167 and the income risk obtained by the Coefficient of Variation (CV) of 0.0208 which means that oil palm farming in Polanto Jaya Village has low production risk and income risk.